The Development Pengembangan E-LKPD Berbasis Google Sites Dengan Integrasi Budaya “Njeleng” pada Materi Hakikat dan Peranan Ilmu Kimia - Sura Juddin; Muti'ah Muti'ah; Eka Junaidi (FKIP University of Mataram, 2026)
This research aims to develop an electronic Student Worksheet (e-LKPD) based on Google Sites that integrates the local culture